Kynurenine Pathway in Psoriasis-a Promising Link? - A. Stepaniuk; A. Baran; I. Flisiak (Adis, Springer Healthcare, 2023)
Abstract Psoriasis is a common dermatosis which affects the patient's skin and general well-being because of its link to diseases such as depression, kidney disease and metabolic syndrome. Pathogenesis remains unknown; however, genetic, environmental and immunological factors seem to play a role in the development of the disease. Due to a lack of complete understanding of the psoriasis pathology, effective treatment is yet to be developed. The kynurenine pathway is one of the ways amino acid tryptophan is metabolised. In comorbidities typical for psoriasis such as chronic kidney disease, depression and atherosclerotic alterations in the activation of the kynurenine pathway were observed, which were mainly characterised by higher activity compared to that in healthy individuals. However, the kynurenine pathway has not been thoroughly studied among patients with psoriasis even though increased levels of l-kynurenine, one of the enzymes in the kynurenine pathway, were found in psoriatic skin lesions. Given the unknown pathogenesis of the disease, this finding seems to be a potential new field of study and shows a possible link between psoriasis and its comorbidities that could also lead to novel effective treatment for this chronic condition.